Composition of Casuarina leaf litter and its influence on Frankia-Casuarina symbiosis in soil - Sayed, W F; el-Sharouny, H M; Zahran, H H; Ali, W M (Folia microbiologica, 2002)
Plant needles of Casuarina equisetifolia were collected and analyzed in parallel with soil analysis. In three strains of Frankia--symbionts of Casuarina--their infectivity and plant performance was determined in vitro after soil amendment with different leaf litter concentrations. Only one strain was able to nodulate the plant at all litter concentrations (0.5, 3 and 5%) although the nodules were very small. However, all treated plants grew poorly; their growth was reduced by approximately 90% (for 5% litter concentration) compared to plants grown on untreated soil, on the basis of total dry mass. Inhibition of nodulation can be attributed to high concentrations of some elements and compounds that were either found in C. equisetifolia litter or originally found in soil (i.e. chloride, cyanide, copper, manganese and phenols). In general, plant growth decreased as more litter was added. Plant total nitrogen content was also reduced after increasing the litter concentration. The inhibitory effect of high litter concentrations was mainly on plant growth and to a lesser extent on plant nodulation by Frankia strains.
Keywords: Phenols; Symbiosis; stromy; Plant Leaves; látky znečišťující půdu; Soil Pollutants; Trees; fenoly; symbióza; kovy; Frankia; Magnoliopsida; Metals; listy rostlin; půdní mikrobiologie; Soil Microbiology